Bax Is Activated during Rotavirus-Induced Apoptosis through the Mitochondrial Pathway - Martin-Latil, Sandra (American Society for Microbiology, 2007)
Rotaviruses are the leading cause of infantile viral gastroenteritis worldwide. Mature enterocytes of the small intestine infected by rotavirus undergo apoptosis, and their replacement by less differentiated dividing cells probably leads to defective absorptive function of the intestinal epithelium, which, in turn, contributes to osmotic diarrhea and rotavirus pathogenesis. Here we show that infection of MA104 cells by the simian rhesus rotavirus strain RRV induced caspase-3 activation, DNA fragmentation, and cleavage of poly(ADP-ribose) polymerase; all three phenomena are features of apoptosis. RRV induced the release of cytochrome c from mitochondria to the cytosol, indicating that the mitochondrial apoptotic pathway was activated. RRV infection of MA104 cells activated Bax, a proapoptotic member of the Bcl-2 family, as revealed by its conformational change. Most importantly, Bax-specific small interfering RNAs partially inhibited cytochrome c release in RRV-infected cells. Thus, mitochondrial dysfunction induced by rotavirus is Bax dependent. Apoptosis presumably leads to impaired intestinal functions, so our findings contribute to improving our understanding of rotavirus pathogenesis at the cellular level.